Appropriateness of oral anticoagulants for the long-term treatment of atrial fibrillation in oder people: results of an evidence-based review and international consensus validation process (OAC-FORTA 2016) - Wehling, Martin (Drugs & aging, 2017)
Background: Age appropriateness of anticoagulants for stroke prevention in atrial fibrillation is uncertain. Objective: To review oral anticoagulants for the treatment of atrial fibrillation in older (age >65 years) people and to classify appropriate and inappropriate drugs based on efficacy, safety and tolerability using the Fit-fOR-The-Aged (FORTA) classification. Methods: We performed a structured comprehensive review of controlled clinical trials and summaries of individual product characteristics to assess study and total patient numbers, quality of major outcome data and data of geriatric relevance. The resulting evidence was discussed in a round table with an interdisciplinary panel of ten European experts. Decisions on age appropriateness were made using a Delphi process. Results: For the eight drugs included, 380 citations were identified. The primary outcome results were reported in 32 clinical trials with explicit and relevant data on older people. Though over 24,000 patients aged >75/80 years were studied for warfarin, data on geriatric syndromes were rare (two studies reporting on frailty/falls/mental status) and missing for all other compounds. Apixaban was rated FORTA-A (highly beneficial). Other non-vitamin K antagonist oral anticoagulants (including low/high-intensity dabigatran and high-intensity edoxaban) and warfarin were assigned to FORTA-B (beneficial). Phenprocoumon, acenocoumarol and fluindione were rated FORTA-C (questionable), mainly reflecting the absence of data. Conclusions: All non-vitamin K antagonist oral anticoagulants and warfarin were classified as beneficial or very beneficial in older persons (FORTA-A or -B), underlining the overall positive assessment of the risk/benefit ratio for these drugs. For other vitamin-K antagonists regionally used in Europe, the lack of evidence should challenge current practice.
First Online: 10 May 2017
Gesehen am 13.06.2018